2022
DOI: 10.1162/edfp_a_00331
|View full text |Cite
|
Sign up to set email alerts
|

In-State Tuition Policies and the College Decisions of Undocumented Students: Evidence from Colorado

Abstract: We study the effects of a decrease in college tuition on college application and enrollment behavior. Specifically, we use student-level data to analyze a Colorado law that granted in-state tuition to undocumented students residing in Colorado. We find an increase in the credit hours and persistence of newly enrolled and likely undocumented students. We do not find evidence of changes in the persistence or credit hours of continuing students. Leveraging application-level data, we show suggestive evidence that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…We identified one policy, Colorado’s extension of in-state tuition to undocumented students who graduated on or after 1 September 2013. However, the policy’s impact appears to have been modest in size and concentrated among undocumented high school students who already had or would graduate high school ( 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…We identified one policy, Colorado’s extension of in-state tuition to undocumented students who graduated on or after 1 September 2013. However, the policy’s impact appears to have been modest in size and concentrated among undocumented high school students who already had or would graduate high school ( 42 ).…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, a tuition reduction in Texas increased enrollment at non-flagship universities by 11 to 18 percentage points but did not increase enrollment at the state's flagship univer-sities (Dickson and Pender, 2013). Meanwhile in Colorado, using student-level data, Grosz and Hines (2022) show that among undocumented immigrants the education policy increased the number of applications, number of credit hours, and student retention from freshman to sophomore year.…”
Section: Policy Effects On College Enrollment and Our Contributionsmentioning
confidence: 96%
“…These impact studies underscore the importance of providing subsidized tuition to undocumented students that have often times lived their entire life in the state and attended public schools. The studies overwhelmingly find a positive overall effect of the policies, with recent studies finding that the policies do not just impact enrollment for these students but also find increases in credit hours and persistence (Grosz & Hines, 2022). However, researchers have found that statelevel policy can be interpreted differently by institutional actors who seek to restrict the policy and others who search for loopholes or ways to deem more students eligible for inclusion (Castrello ´n, 2022;Nienhusser, 2018).…”
Section: State-level Factorsmentioning
confidence: 99%